Analisis Sistem Kerja Unit Pengelolaan Hasil (UPH) Kopi Sinar Tani Berbasis Model Value Chain Porter - Maria Helena Chandra; Nasarius Innosensius Peja Lodo (Yayasan Literasi Sains Indonesia, 2026)
This study aims to examine the operational system of UPH Kopi Sinar Tani in Ngadhamana Village, Bajawa District, Ngada Regency, using Michael Porter’s value chain evaluation model. The study is motivated by need to develop a comprehensive understanding of how primary and support activities in smallholder coffee management are organized and how they contribute to value creation at the community level. Village-based coffee processing units are often approached in a fragmented manner, particularly with focus on production, which limits analysis of interconnections among stages within value chain. Employing qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and document analysis. Data were analyzed by mapping inbound logistics, operations, outbound logistics, marketing and sales, and service activities, along with supporting activities surrounding them. The findings indicate that UPH Kopi Sinar Tani has developed a community-based value chain, with notable strengths in post-harvest management, farmer partnership relations, and collective working practices. However, limitations remain in strengthening marketing functions, cost recording systems, and managerial capacity. Theoretically, this study extends the application of Porter’s value chain model to the context of rural, community-based coffee enterprises and provides an analytical foundation for formulating strategies aimed at enhancing value added and the sustainability of smallholder coffee processing units.